(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Review the clinical and paraclinical characteristics and treatment results of patients with primary immune thrombocytopenia at Nghe An General Friendship Hospital in 2023. Research methods: A descriptive study reported a series of cases of 53 patients with primary immune thrombocytopenia treated at the Department of Clinical Hematology, Nghe An General Friendship Hospital, from January to December 2023. Research results: The average age in the study group was 50.6± 21.8 years old; The most common age group is 35-60 years old, accounting for 35.8%; Females account for a high rate of 81.1%; male/ female ratio = 1/4.3. Clinical characteristics: 96.2% (51/53) of patients were hospitalized for bleeding reasons; Spontaneous bleeding accounts for a high rate of 98.1%, of which simple subcutaneous bleeding accounts for the highest rate of 69.8%; Polymorphic haemorrhage forms account for the majority (79.2%). Paraclinical characteristics: The average platelet count at admission was 11.3 ± 8.4; 45.28% of patients had mild anaemia. The primary treatment regimen is conventional corticosteroids, accounting for 94.3%; The response rate to traditional corticosteroid regimens is 94.3%. Conclusion: Primary immune thrombocytopenic is expected in the age group of 35 - 60 years old, with spontaneous bleeding, subcutaneous bleeding and simple bleeding forms accounting for the main proportion. Patients have a high response rate to treatment, with younger age groups responding lower than middle-aged and elderly groups.